The impact of triglyceride-glucose index on incident cardiovascular events during 16 years of follow-up: Tehran Lipid and Glucose Study - Barzegar, Niloofar (Cardiovasc Diabetol, 2020)
BACKGROUND: To investigate whether the Triglyceride-Glucose index (TyG-index) is associated with increased risk of cardiovascular diseases (CVD)/coronary heart disease (CHD). METHODS: A total of 7521 Iranians aged ≥ 30 years (male = 3367) were included in the study. Multivariate Cox regression analyses (adjusted for age, gender, waist circumference, body mass index, educational level, smoking status, physical activity, family history of CVD, type 2 diabetes, hypertension, low and high density lipoprotein cholesterol, and lipid lowering drugs) were used to assess the risk of incident CVD/CHD across quintiles and for 1-standard deviation (SD) increase in the TyG-index. The cut off point for TyG-index was assessed by the minimum value of [Formula: see text] . We also examined the added value of the TyG-index in addition to the Framingham risk score when predicting CVD. RESULTS: During follow-up, 1084 cases of CVD (male = 634) were recorded. We found a significant trend of TyG-index for incident CVD/CHD in multivariate analysis (both Ps for tend ≤ 0.002). Moreover, a 1-SD increase in TyG-index was associated with significant risk of CVD/CHD in multivariate analysis [1.16 (1.07–1.25) and 1.19 (1.10–1.29), respectively]. The cut-off value of TyG-index for incident CVD was 9.03 (59.2% sensitivity and 63.2% specificity); the corresponding value of TyG-index for incident CHD was 9.03 (60.0% sensitivity and 62.8% specificity), respectively. Although no interaction was found between gender and TyG-index for CVD/CHD in multivariate analysis (both Ps for interaction > 0.085), the significant trend of TyG-index was observed only among females for incident CVD (P = 0.035). A significant interaction was found between age groups (i.e. ≥ 60 vs < 60 years) and TyG-index for CVD outcomes in the multivariate model (P-value for interaction = 0.046). Accordingly, a significant association between the TyG-index and outcomes was found only among the younger age group. Among the population aged < 60 the addition of TyG-index to the Framingham risk score (FRS) did not show improvement in the predictive ability of the FRS, using integrated discrimination improvement. CONCLUSION: The TyG-index is significantly associated with increased risk of CVD/CHD incidence; this issue was more prominent among the younger population. However, adding TyG-index to FRS does not provide better risk prediction for CVD.